(untitled) (Global Journals of Research in Engineering, 2023)
This article describes the methodology for assessing the energy efficiency of pumping systems equipped with a variable electric drive and operating with variable load which was elaborated by the authors of the article The analysis of traditional methods of recalculating the characteristics of the efficiency of pumping units when changing the frequency of rotation of the impeller using the formulas of theories of hydrodynamic similarity of blade blowers is presented It is shown that in the derivation of the similarity formulas assumptions were made which were not fully confirmed later when testing operating pumps An algorithm and a technique developed by the authors are presented that allow one to read the actual values of the efficiency from the pre-digitized universal characteristics of vane blowers The results of comparison of efficiency values calculated by different methods are presented It is shown that when the current impeller speed deviates from the nominal one by more than 10 there is a steady tendency to exceed the efficiency values obtained using the formulas of hydrodynamic similarity in relation to its values read from the universal characteristics Calculations are given for comparing the energy efficiency of pumping systems for various methods of calculating their efficiency and the control method It is shown that the use of similarity formulas to recalculate the efficiency leads to an overestimation of the estimated energy efficiency of the pumping systems and the adoption of insufficiently substantiated investment decisions